KAJIAN KELAYAKAN EKONOMI JARINGAN TAMBAK GARAM LEPAS PANTAI DI SAMPANG MADURA - Adimas Candra Anugrah; Samuel Hasudungan; Suharyanto Suharyanto; Robert J. Kodoatie (Jurnal Karya Teknik Sipil, 2015)
Sampang regency of East Java Province is one of the salt-producing regions. The lack of salt ponds in Indonesia is resulting in low national salt production. In an effort to expand the salt ponds, to increase national salt production and to improve quality of the salt, the salt ponds are planned in offshore Sampang. The potential land in an area Sampang is + 757 ha, the planned area of this thesis is + 225 ha. In this design, the design standards used are salt production system in Korea, with the ratio of the reservoir : evaporation area : crystallization area = 5: 3: 2, water supply systems by utilizing tidal and other structures planning such as dikes, warehouse, and sluice. At the beginning of the design conducted is by making a plot pond layout, continued by design dimensions and elevation on the pond construction, bozem, peminihan, and table salt, so the water availability can be guaranteed. From the location of the planned area of + 225 ha is divided into 19 modules area of 10 hectares, designed reservoir 5 ha, evaporation area 3 ha, and crystallization area 2 ha. In accordance with the criteria of the salt pond water depth according to the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia, for the water level in reservoir is 70 cm, height of water on evaporation area is 35 cm, and the height of water on crystallization area is 12 cm. By using this system, salt production is expected to rise from +100 tons / ha / year to + 230 tons / ha / year. Sea wall is planned along the + 5.5 km, making of the pond embankment is planned to use as much concrete buis 315,000 and built 19 warehouses. The cost of making an offshore salt pond area of + 225 ha is in the range of Rp. 3,138,717,259,336,00 with IRR point 16,25 % and Payback period for 8 years